PUBLIC SERVICE REFORM IN IMPROVING COOPERATIVE PERFORMANCE: Case Study of Sido Makmur Multi-Business Cooperative, Surabaya City - Janah, Machfira Miftahul (MAP Observer: Jurnal Penelitian Administrasi Publik, 2022)
Basically, people really need a service system that has changed, with the renewal system in service, the community will feel satisfied with the services that have been provided to government agencies. With the existence of public service reforms in improving performance, the community hopes that the services provided by the institution do not make people feel burdened by convoluted services or cut off the bureaucracy. Based on observations or research conducted by the writer using qualitative descriptive research. Primary data collection is done through interviews, observation, documentation and secondary data, namely literature study is used to strengthen research. the author's target in the study is the Cooperative Aneka Usaha Sido Makmur.